SIMULAÇÃO DE BAIXA FIDELIDADE COMO METODOLOGIA DE ENSINO PARA GRADUANDOS DE ENFERMAGEM - Turra, Luana; Zieher, Petra; Viana de Sousa Bittencourt, Gisele Cristiane; Triquez, Simone Luciana; Letti, Anne Cristine (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
Introduction: Clinical simulation is understood as a valuable pillar in health education, enabling the development of various skills (NEGRI et al., 2019). Teachers need to appropriate these tools. In this sense, adopting new teaching and learning strategies in health and nursing is essential for excellence in the development of knowledge, skills and attitudes (NASCIMENTO et al., 2020). Objective: To report the experience of nurses supervising internships and practical classes of nursing graduation in the face of the use of low-fidelity simulation in teaching critical patient care. Method: This is an experience report whose motivation began after the use of low-fidelity simulation in critical patient care. Practical classes were taught by nurses in the first semester of 2021. 60 undergraduate nursing students from different phases of the course participated in the simulations. Students were divided into groups of 4 to 5 students, received the clinical case with important data for the conducts in the scene and then were sent to the low-fidelity scenario. The performance in the scenario lasted around 15 minutes per group and was observed by all professors who did not interfere with the progress. Subsequently, there was a debriefing where the academics talked about how they felt during the performance and points of improvement they observed. Results: It was observed that the low-fidelity clinical simulation provides the students with a better posture, because when faced with a potentially real situation, they position themselves as future professional nurses. Anxiety about the setting and the performance of activities was brought up by several students. Weakness was evidenced in relation to dexterity and decision-making in some students. Feedback regarding the method was mostly positive. Conclusion: The low-fidelity simulation used in the teaching-learning process of nursing students is a very rich methodology, which subsidizes teaching tools beyond theoretical knowledge, involving practical, leadership and even emotional aspects.